Matching the training program to the natural athlete life-cycle: Practical coaching recommendations for effective long-term athlete development (LTAD) and competitive longevity - Wilson, G. (Journal of Australian Strength and Conditioning, 2017)
The purpose of this paper is to provide practical recommendations for coaches to implement in relation to matching the training program to their athlete`s natural life-cycle. This paper presents 5 case studies, analyzing the competitive performance data from 4 elite Indonesian Olympic weightlifting athletes, and Jamaican sprint super-star Usain Bolt. The analysis demonstrates that there are typically 4 distinct phases in an athlete`s normal life-cycle: (1) The Preparatory Phase (PP) (approximate ages 12 to 16-years); (2) The Rapid Development Phase (RDP) (approximate ages 17 to 22- years); (3) The Maintenance Phase (MP) (approximate ages 23-28-years); and (4) The Deterioration Phase (DP) (approximate ages 29 and above). As all athletes are individuals, each coach is encouraged to determine their athletes phase based on competition performances achieved over time. In each of these phases the capacity of the athlete to improve their competitive performance is quite different, and this change in capacity should be reflected in a change in the intensity and volume of training performed. While the typical 8-10 intense training session per week may well be optimally suited to the RDP; lower training volumes and intensities are recommended for the MP (4-6 weekly training sessions) and DP (3-5 weekly training sessions), with a greater emphasis placed on recovery and rest for these older athletes. Through carefully matching the training program to the correct phase of the athlete`s natural life cycle, it is proposed that the athlete will be able to continue to compete at a higher level for longer and experience lower rates of injury.